A Protocol of Intradialytic Exercise for Improvements in Inflammatory Status, Body Composition, and Functional Capacity - Lopes, Lorena Cristina Curado; Monteiro, Paula Alves [UNESP]; Mota, João Felipe (Springer Nature, 2022)
Skeletal muscle wasting has been well-documented among hemodialysis patients. This catabolic condition can be induced by numerous factors, including low-grade inflammation, and is associated with impairments in functional capacity and quality of life, as well as an increased mortality risk. We previously showed that 12 weeks of intradialytic resistance training increases lean mass, functional capacity, and the quality of life of hemodialysis patients. This chapter provides the details of a protocol of intradialytic exercise that leads to improvements in inflammatory status, body composition, and functional capacity.
Keywords: Chronic kidney failure; Cytokines; Dialysis; Exercise; Physical performance; Quality of life; Resistance training